Evicting the poor in the 'overriding public interest': Crisis of rights and interests, and contestations in Nigerian cities. (June 2020) - Onyebueke, Victor Udemezue; Walker, Julian; Lipietz, Barbara; Ujah, Oliver; Ibezim-Ohaeri, Victoria
Abstract: Forced eviction is unquestionably a global humanitarian crisis. Africa and, particularly, Nigeria bear a major brunt of this 'global epidemic', which carries enormous material and human costs. Yet, eviction is frequently hidden behind forms of displacements which operate within the law, and are justified on the basis of public interest rationales. Drawing on a research project into urban infrastructure-related displacement in Nigeria, this paper explores the reported incidence, patterns and trends of urban displacements and their impacts in Nigeria over a period of six years (2010–2016). Through the prism of the holistic approach, it interrogates the conflicting 'publics' and 'interests' in the diverse displacement contexts, and argues that the 'public interest' behind official rationale for displacement is, in reality, a highly contested affair. The paper recommends that displacements, where unavoidable, ought to be planned inclusively against the background of meaningful engagement and procedural safeguards. Highlights: Nigeria witnessed about 370 cases of reported displacements between 2010 and 2016. Displacement patterns and trends are uneven between southern and northern Nigeria. Highest rates of reported displacement in Nigeria occur in Abuja and Lagos. Norms for acceptable outcomes vary over time between displacers and displacees.